POSITIONING THE WORD 'LUGHATAN' AS HAL: المسألة في ترجيح كون "لغة" حالًا - Jamal, Danial (Al Mihwar: Jurnal Pendidikan Bahasa Arab dan Kebahasaan, 2024)
This study examines the use of the word 'lughatan' in everyday language from the past to the present, The word is often positioned (i’rab) as 'al-manshub 'ala naz'i al-khafid' rather than as 'hal'. This research aims to reinforce the classification of 'lughatan' as 'hal' in Arabic sentences and to explain the underlying reasons for this classification. By employing a descriptive-analytical methodology, the study seeks to analize divergent opinions among Nahwu scholars regarding the positioning of 'lughatan', both as 'al-manshub 'ala naz'i al-khafid' and 'hal', and the rationale for these positions. The data analysis concludes that 'lughatan' is appropriately positioned as 'hal' in various Arabic sentence constructions. The justification for this is that positioning should be understood straightforwardly, avoiding unnecessary complexity in the interpretation process.